(untitled) (SCIENCE TIME JOURNAL, 2026)
This research article explores the linguistic, stylistic, and cultural challenges involved in translating Isaac Asimov’s I, Robot (1950) into Russian and Uzbek. Science fiction (SF) poses unique translation problems because of its dense technical vocabulary, imaginative neologisms, and hybrid narrative tone. This study applies a comparative qualitative approach grounded in translation theory — particularly the frameworks of Newmark (1988), Vinay and Darbelnet (1995), and House (2015) — to analyze how translators in two linguistically and culturally distinct contexts interpret Asimov’s speculative world. Using purposive sampling, ten key excerpts from I, Robot were compared across the English, Russian, and Uzbek versions. The analysis focused on the treatment of neologisms, logical modality, stylistic register, and cultural adaptation. Findings reveal that Russian translators generally prioritize semantic fidelity and terminological precision, while Uzbek translators tend toward communicative fluency and cultural domestication. These differences reflect not only linguistic structure but also socio-literary traditions and genre familiarity. The discussion highlights broader implications for translation theory: the need for genre-sensitive strategies, increased translator visibility, and the creation of standardized science fiction terminology in underrepresented languages. This study contributes to translation studies by illustrating how cross-linguistic and cross-cultural translation of speculative fiction exposes the limits of equivalence and the creative potential of linguistic innovation.